Fabrication of transparent MgAl2O4 ceramics by hot-pressing of sol-gel-derived nanopowders. Issue 10 (December 2015) - Balabanov, S.S.; Yavetskiy, R.P.; Belyaev, A.V.; Gavrishchuk, E.M.; Drobotenko, V.V.; Evdokimov, I.I.; Novikova, A.V.; Palashov, O.V.; Permin, D.A.; Pimenov, V.G.
Abstract: An approach to synthesize stoichiometric MgAl2 O4 nanopowders by hydrolysis of magnesium aluminum double isopropoxide MgAl2 (OPr i )8 followed by the low-temperature calcination have been proposed. The evolution of the structural and morphological characteristics of MgAl2 O4 nanopowders calcined in the 900–1200 °С temperature range has been studied. Variation of the annealing conditions allows one to produce high-purity reactive MgAl2 O4 powders with the specific surface area from 10 to 166 m 2 /g. The powder production rate of 1 kg per day was achieved using the home-made laboratory apparatus. Doping by LiF increases crystallinity of spinel powders and reduces their specific surface area due to formation of the liquid phase of lithium fluoride upon calcination. The single-phase MgAl2 O4 : LiF 3 wt% powders with the particle size from the 250–1000 nm range have been consolidated into transparent ceramics ( Т =83.7%) by hot pressing at Т =1600 °C under P ~50 MPa.